Prediction of Wearing out of Power Transformer Winding Insulation - Polyakov, M.A.; Vasilevskij, V.V. (Технічна електродинаміка, 2014)
Importance of the different parameters of wearing out of power transformer insulation prediction structure, operating factors, selection of configuration and parameters of paper insulation and transformer oil technical state models is investigated. Prediction of wearing out of power transformer winding insulation is reduced to the stochastic prediction of load dynamics and ambient temperature, simulation of the changes of technical states of paper insulation and transformer oil, aging calculations and probabilistic estimation of insulation wearing out. Computer simulation of power transformer insulation wearing out for the next ten years of operation is performed. Исследована значимость различных параметров структуры прогноза износа изоляции силового трансформатора, факторов эксплуатации, произведен выбор структуры и параметров моделей технического состояния бумажной изоляции и трансформаторного масла. Прогнозирование износа изоляции обмоток силового маслонаполненного трансформатора сведено к стохастическому прогнозированию динамики нагрузки, температуры окружающей среды, имитационному моделированию изменений технического состояния бумажной изоляции и трансформаторного масла, расчету старения и вероятностной оценке величины износа изоляции. Выполнено компьютерное моделирование износа изоляции силового трансформатора в течение предстоящих десяти лет эксплуатации.